Atravesados : essays on queer Latinx young adult literature - Boffone, Trevor; Herrera, Cristina; Aldama, Frederick Luis, 1969- (Children's Literature Association series., 2025)
"Atravesados: Essays on Queer Latinx Young Adult Literature shows how Latinx queer YA writers discard the "same old story," and offer critical representations of queerness that broaden YA writing and insist on the presence of queer teens of color. Atravesados draws on foundational Chicana queer theorist Gloria Anzaldúa's notion of "atravesados" to speak to the spectrum of queer youth Latinidades as they materialize in YA literature. Los atravesados, according to Anzaldúa, are "The squint-eyed, the perverse, the queer, the troublesome, the mongrel, the mulato, the half-breed, the half dead; in short, those who cross over, pass over, or through the confines of the 'normal.'" Los atravesados reside in the borderlands space of ni de aquí ni de allá, neither here nor there, present yet liminal, their queerness the very source of both frustration and empowerment, a paradox of joy and tragedy. Although written in 1987, Anzaldúa's theory speaks to the realities of queer Latinx teens that fill the pages of YA literature well into the twenty-first century. Characters such as Juliet from Gabby Rivera's Juliet Takes a Breath, Aaron from Adam Silvera's More Happy Than Not, or the titular Chulito from Charles Rice-Gonzales's novel encompass the highs, lows, and everything in-betweenness of queer Latinx teen lived experiences. This collection tells their stories. Contributors speak to the spectrum of queer youth Latinidades as they materialize in YA literature, paying close attention to representation and the ways youth are portrayed-whether accurate or stereotypical. Close attention is paid to books that succeed in broadening the field of YA, highlighting authors that draw from their own lived experiences and situate strong, fully developed characters. Taken together, these essays move beyond the page, explaining to readers why representation and authenticity matter in YA literature, as well as the far-reaching effects they can have for real world queer Latinx teens"--